TRAINING ON PREPARING FINANCIAL REPORTS FOR MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) USING THE BUKU WARUNG (BURUNG) APPLICATION IN BITAI VILLAGE, JAYA BARU SUBDISTRICT, BANDA ACEH CITY - Susanti, Eva; Sartika, Fani; Syawalina, Cut Fitrika; Zhira, Aulia Anna (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2025)
This particular community service activity was implemented in the form of training on the preparation of financial reports for Micro, Small, and Medium Enterprises (MSMEs) using the “Buku Warung” (BURUNG) application in Bitai Village, Jaya Baru Subdistrict, Banda Aceh City. In the current digital era, financial bookkeeping has become much easier, one of which is through the use of the Buku Warung (BURUNG) application. BURUNG is an MSME bookkeeping application designed to help business owners record their financial transactions more easily. This community service program was carried out over a period of six months. The methods used in this program included training and mentoring on how to use the Buku Warung (BURUNG) application. The results of this program showed that MSME actors were very enthusiastic about participating in the financial report preparation training using this application. Furthermore, through this community service activity, the local community—particularly MSME owners—gained the skills to prepare their business financial reports more accurately and effectively.Keywords: Financial reports, Buku warung